Two sporulated Bacillus enhance immunity in Galleria mellonella protecting against Candida albicans - de Barros, Patrícia Pimentel [UNESP] (2019)
The aim of this study was to evaluate the effects of Bacillus subtilis and Bacillus atrophaeus on Galleria mellonella immunity challenged by Candida albicans. Firstly, we analyzed the susceptibility of G. mellonella to bacilli (vegetative and sporulating forms). It was found that both vegetative and sporulating forms were not pathogenic to G. mellonella at a concentration of 1 × 104 cells/larva. Next, larvae were pretreated with two species of Bacillus, in the vegetative and sporulating forms, and then challenged with C. albicans. In addition, the gene expression of antimicrobial peptides (AMPs) such as Gallerimycin, Gloverin, Cecropin-D and Galiomicin was investigated. Survival rates increased in the Bacillus treated larvae compared with control larvae inoculated with C. albicans only. Cells and spores of Bacillus spp. upregulated Gloverin, Galiomicin and Gallerimycin genes in relation to the control group (PBS + PBS). When these larvae were infected with C. albicans, the group pretreated with spores of B. atrophaeus and B. subtilis showed a greater increase in expression of Galiomycin (49.08-fold and 13.50-fold) and Gallerimycin (27.88-fold and 68.15-fold), respectively, compared to the group infected with C. albicans only (p = 0.0001). After that, we investigated the effects of B. subtilis and B. atrophaeus on immune system of G. mellonella evaluating the number of hemocytes, quantification of melanization, cocoon formation and colony forming units (CFU) count. Hemocyte count increased in response to stimulation by Bacillus, and a higher increase was achieved when larvae were inoculated with B. subtilis spores (p = 0.0011). In the melanization assay, all groups tested demonstrated lower production of melanin compared to that in the phosphate-buffered saline (PBS) group. In addition, full cocoon formation was observed in all groups analyzed, which corresponded to a healthier wax worm. Hemolymph culture revealed higher growth of B. atrophaeus and B. subtilis in the groups inoculated with spores. We concluded that spores and cells of B. atrophaeus and B. subtilis stimulated the immune system of G. mellonella larvae and protected them of C. albicans infection.